2019
DOI: 10.1371/journal.pone.0225967
|View full text |Cite
|
Sign up to set email alerts
|

Does seed size mediate sex-specific reproduction costs in the Callosobruchus maculatus bean beetle?

Abstract: There is a trade-off between reproductive effort and adult longevity, and when resource allocation is taken into account, it is especially pronounced in species that have aphagous adult forms. This trade-off may be further complicated by environmental factors such as nutrient availability during larval development and by the other sex, which influences the costs of reproduction due to the presentation of nuptial gifts. Here, we examined the influence of larval nutrient quantity on the sex-specific longevity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…To eliminate the potential effects of nutrient limitations, at this stage, we excluded the smallest seeds (less than approximately 150 mg). While multiple C. maculatus larvae can develop inside a single cowpea seed, our previous results suggested that the effects of seed size variation on adult phenotypes cannot be ignored, even if a single larva develops inside a seed [ 33 ]. Each egg-bearing seed was placed in a separate Eppendorf tube with a perforated lid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate the potential effects of nutrient limitations, at this stage, we excluded the smallest seeds (less than approximately 150 mg). While multiple C. maculatus larvae can develop inside a single cowpea seed, our previous results suggested that the effects of seed size variation on adult phenotypes cannot be ignored, even if a single larva develops inside a seed [ 33 ]. Each egg-bearing seed was placed in a separate Eppendorf tube with a perforated lid.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies in C. maculatus showed that reproductive activity reduces the lifespan of males [ 32 ]; at the same time, females benefit from mating with either virgin males [ 32 ] or mating multiple times during their lifespan [ 28 ]. There is evidence that the size of a gift has quantitative effects on the fitness of C. maculatus , with larger gifts corresponding to better survival among recipient females but worse survival among donor males [ 33 ]. Importantly, the ejaculate of C. maculatus has been shown to provide females with water [ 34 , 35 ], which suggests another function of ejaculate: Water supply for females.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the female costs, nuptial gifts are typically an energy-intensive reproductive strategy for males. Nuptial gift production can increase male mortality (Małek et al 2019; Perry & Tse 2013) and reduce male courtship quality (del Castillo & Gwynne 2007), and even simply carrying nuptial gifts can significantly increase male energy expenditure (Prokop & Okrouhlik 2021). Both endogenous fluid and exogenous prey have high production demands which often leads to selective pressures to maximise the gift efficiency and efficacy through various strategies, including deceiving females or plastically altering gifts in response to female quality (Albo et al 2019; Beyer et al 2021; Ghislandi et al 2018; Martínez-Villar et al 2023; Pandulli-Alonso et al 2021; Solano-Brenes et al 2021; Stålhandske 2002).…”
Section: Introductionmentioning
confidence: 99%